2021
DOI: 10.1186/s40792-021-01346-w
|View full text |Cite
|
Sign up to set email alerts
|

Hypothyroidism and hypopituitarism as immune-related adverse events due to lenvatinib plus pembrolizumab therapy in the immediate postoperative period after laparoscopic hepatectomy for liver metastases from gastric cancer: a case report

Abstract: Background Immune checkpoint inhibitors (ICIs) are emerging agents used for the treatment of various malignant tumors. As ICIs are generally used for unresectable malignant tumors, there have been only a few reports of patients who underwent surgery after receiving these drugs. Therefore, it remains unclear how immune-related adverse events (irAEs) affect the postoperative course. Here, we report a patient with advanced gastric cancer who underwent laparoscopic hepatectomy for liver metastases … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
14
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 21 publications
0
14
0
Order By: Relevance
“…It is well known that patients who respond to ICI tend to develop irAEs (5). Kimimasa present a case of laparoscopic hepatectomy after receiving lenvatinib plus pembrolizumab and developed hypothyroidism and hypopituitarism after surgery, the patient treated with ICIs and responded effectively to ICI therapy before surgery (21). We need to explore whether liver metastasis is associated with the occurrence of irAEs.…”
Section: Discussionmentioning
confidence: 99%
“…It is well known that patients who respond to ICI tend to develop irAEs (5). Kimimasa present a case of laparoscopic hepatectomy after receiving lenvatinib plus pembrolizumab and developed hypothyroidism and hypopituitarism after surgery, the patient treated with ICIs and responded effectively to ICI therapy before surgery (21). We need to explore whether liver metastasis is associated with the occurrence of irAEs.…”
Section: Discussionmentioning
confidence: 99%
“…It is established that patients who respond to ICI tend to develop irAEs 5 . Kimimasa presented a case of laparoscopic hepatectomy after receiving lenvatinib plus pembrolizumab, in which the patient developed hypothyroidism and hypopituitarism after surgery; the patient was treated with ICIs and responded effectively to ICI therapy before surgery 21 . The association between liver metastasis and occurrence of irAEs needs to be explored further.…”
Section: Discussionmentioning
confidence: 99%
“…However, in that case, the patient was misdiagnosed as advanced lung cancer instead of resectable lung cancer. Sasaki et al 23 reported a case of laparoscopic hepatectomy after receiving lenvatinib plus pembrolizumab and developed hypothyroidism and hypopituitarism after surgery. Regarding surgery after neoadjuvant chemoimmunotherapy, it is essential to recognize that irAEs might occur in the postoperative period.…”
Section: Discussionmentioning
confidence: 99%